Experimental and numerical study on thermal performance of Li(NixCoyMnz)O2 spiral-wound lithium-ion batteries. (25th June 2018) - Yang, Xiaolong; Yang, Pengfei; Zhang, Zeping; Duan, Yongkang; Hu, Jihao
Highlights: Battery non-uniform temperature distribution is shown using thermal imaging at 5 C. The electric resistances of the battery cap and jelly roll are studied. Heat generation analysis helps explain the causes of battery temperature gradient. A multi-component thermal model is built and validated. Abstract: A clear understanding of thermal properties of lithium-ion batteries and their effects on battery performance is vital to design thermal management systems. The thermal characteristics of a commercial 18, 650 Li(NixCoyMnz)O2 Lithium-ion battery is studied under constant current discharge rates of 1 C, 2 C, 3 C, 4 C, and 5 C. Infra-red (IR) images are captured during experiments with a Tix520 Thermal imager at various discharge rates. And temperature variations at different position of the battery surface at different discharge C-rates are investigated. In addition, the internal resistances of the battery cap, jelly roll and their influence on the heat generation are also discussed. The results show that the variation of the surface temperature of the battery at high rates (3 C, 4 C, 5 C) is different from low rates (1 C, 2 C) during discharging. The temperature difference at high rates is up to 6 °C. The volumetric heat generation rate of the cap is much higher than the jelly-roll's, which is up to 2.2 × 10 5  W/m 3 at 1 C. At last, a 3D multi-component thermal model is present to simulate the thermal behaviors of the battery. The multi-component numerical model can present the thermal characteristics of different battery parts at different discharge rates and thus good consistence with experiment data.